Hypothetical Learning Trajectory In The Material Of Ordering Fractions - Widianti, Hesti Dwi; Mohammad Faizal Amir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Learning to order fractions is often challenging for elementary school students because they have not yet understood the relationship between the numerator, the denominator, and the value of a fraction. This study aims to develop and examine a Hypothetical Learning Trajectory (HLT) designed to support fourth-grade students in understanding fraction ordering through a series of gradual activities, ranging from concrete to symbolic. The study employed a qualitative approach using Design-Based Research (DBR). Data were collected through observations, student worksheets, and documentation of the learning process. The findings show that the HLT contributed to improving students’ understanding, as reflected in their ability to identify equivalent fractions, find common denominators, use least common multiples (LCM), and order fractions with both equal and different denominators. These results indicate that HLT is an effective instructional approach that enhances the quality of fraction learning in elementary schools.